Danos do percevejo marrom Euschistus heros (F.) (Hemiptera: Pentatomidae) em soja - Scopel, Wanessa (2012)
The management of stink bugs should be performed based on the level of action, but the development of new soybean cultivars with different cycle characteristics, growth habits and yield potential, demand that the criteria used for decision making regarding the application of insecticides should be reviewed. Five experiments were conducted, four in the experimental area of the University of Passo Fundo and one at the headquarters of Embrapa Wheat in Passo Fundo, during the 2011/2012 season, aiming to evaluate the effect of infestation by different population levels of the Neotropical brown stink bug E. heros (F.), on different growth stages of the plants on yield and quality of soybean seeds. It was found that the infestation of 12 bugs/m, for 21 days during the vegetative stage (V6) did not affect grains yield; infestations of 4 bugs/m for 10 days at the beginning of seed development (R5) reduced grain yield, this did not occur with same density at the beginning of flowering (R1) and density of 2 bugs/m, at the early development of pods (R3); density of 12 bugs/m at the end of the reproductive period (R6), regardless the duration of infestation (7, 14 and 21 days), reduced seed quality but did not affect grain yield; infestations did not cause leaf retention at any population levels and growth stages evaluated.